2022
DOI: 10.3390/ijerph19159146
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices concerning Black Fungus during COVID-19 Pandemic among Students of Bangladesh: An Online-Based Cross-Sectional Survey

Abstract: Background: Infection with COVID-19 and its control entailing steroids and immunomodulatory medications disrupted normal immune function. The ensuing immunological disorder led to the rise of another infection—Black Fungus (Mucormycosis). However, the spread of Black Fungus can be minimized through proper knowledge, informed attitude, and conscious preventive practice. This study aimed to assess students’ knowledge, attitude, and practice (KAP) regarding Black Fungus amid the COVID-19 pandemic in Bangladesh. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
(64 reference statements)
2
6
0
Order By: Relevance
“…4 Study conducted by Islam et al among students to assess their KAP regarding black fungus showed that the knowledge about black fungus among 32.9% of their students was low and 26% had high scores. 5 In the present study, we find that 82.4% of the participants had heard about black fungus.…”
Section: Resultssupporting
confidence: 46%
“…4 Study conducted by Islam et al among students to assess their KAP regarding black fungus showed that the knowledge about black fungus among 32.9% of their students was low and 26% had high scores. 5 In the present study, we find that 82.4% of the participants had heard about black fungus.…”
Section: Resultssupporting
confidence: 46%
“…Later, the score for each category was re-categorized into three levels, namely low, moderate, and high score. Finally, quartiles were used to classify the total score: up to the 25 th quartile was a low score, 26 th to 75 th quartile was a moderate score and more than the 76 th quartile was a high score in every module (knowledge, attitude, and practice) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were: (i) a student enrolled in a Bangladeshi university and (ii) having the ability to read the instruction and write the response online using standard English. Considering the aforementioned criteria, the university students were approached, and using the purposive snowball sampling technique each participant was requested to forward the e-questionnaire to friends and others in their peers [11,20,[32][33][34][35][36]. A total of 887 responses were studied for this study after careful scrutiny.…”
Section: Study Settings and Participantsmentioning
confidence: 99%
“…A further infection known as Black Fungus (Mucormycosis) emerged as a result of the immune dysfunction that followed. However, with the right information, a knowledgeable mindset, and deliberate preventive behavior, the spread of black mold can be reduced [ 7 ]. Due to a dearth of population-based studies, it is uncertain how common mucormycosis is in India.…”
Section: Introductionmentioning
confidence: 99%